2002
DOI: 10.2337/diabetes.51.5.1588
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of 8-Hydroxy-2′-Deoxyguanosine and Mitochondrial DNA Deletion in Kidney of Diabetic Rats

Abstract: Oxidative stress may contribute to the pathogenesis of diabetic nephropathy. However, the detailed molecular mechanism remains uncertain. Here, we report oxidative mitochondrial DNA (mtDNA) damage and accumulation of mtDNA with a 4,834-bp deletion in kidney of streptozotocin-induced diabetic rats. At 8 weeks after the onset of diabetes, levels of 8-hydroxy-2-deoxyguanosine (8-OHdG), which is a marker of oxidative DNA damage, were significantly increased in mtDNA from kidney of diabetic rats but not in nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
130
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(150 citation statements)
references
References 49 publications
14
130
1
1
Order By: Relevance
“…STZ increased ROS and declined oxidation resistance in mice. In diabetes, excess ROS in the body attacks DNA and produces 8-OHdG as an indicator of DNA oxidative damage [26]. Our results showed 8-OHdG and MDA levels in T2D mice far beyond those in the normal group, which is consistent with the results by Pan et al [27].…”
Section: Discussionsupporting
confidence: 93%
“…STZ increased ROS and declined oxidation resistance in mice. In diabetes, excess ROS in the body attacks DNA and produces 8-OHdG as an indicator of DNA oxidative damage [26]. Our results showed 8-OHdG and MDA levels in T2D mice far beyond those in the normal group, which is consistent with the results by Pan et al [27].…”
Section: Discussionsupporting
confidence: 93%
“…Notably, we first determined that the salivary 8-OHdG levels of periodontitis patients with deleted mtDNA were significantly higher than those of patients with non-deleted mtDNA and that there was a positive correlation between salivary 8-OHdG level and the occurrence of the 5-kbp mtDNA deletion in diseased gingival tissues. Similar correlations were previously reported by Kakimoto et al (Kakimoto et al 2002) and Suzuki et al (Suzuki et al 1999) in their studies on the association between oxidative DNA damage and diabetes.…”
Section: Discussionsupporting
confidence: 90%
“…Oxidative DNA damage is reported to be involved in the pathogenesis of many chronic conditions, including neurodegenerative disease (Wang et al 2008), diabetes (Kakimoto et al 2002), cancer (Wada et al 2006), and chronic inflammatory conditions (Dincer et al 2007). However, information on markers of ROS reactions with DNA in periodontitis is limited.…”
Section: Discussionmentioning
confidence: 99%
“…25 Additional studies have shown that urinary 8-OHdG correlated with the severity of DN and retinopathy 27 and also with future development of DN. 28 Others 29 have shown that in streptozotocin-induced diabetic rats, measurement of levels of 8-OHdG from mitochondrial DNA was higher in both renal cortices and papillae and so were the urinary 8-OHdG levels. In contrast, the levels of 8-OHdG in nuclear DNA were not elevated.…”
Section: Discussionmentioning
confidence: 99%